Penerapan Anfis Untuk Menentukan Zona Gangguan Pada Saluran Tansmisi Tenaga Listrik - Budiman, Dzaki; Zakri, Azriyenni Azhari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
This research proposes one method in determining distance relay fault zones in power transmission systems. This research uses software simulated using Matlab / Simulink R2016a for asymmetric short circuit fault that produces voltage and current for each phase. The result of that fault will uses intelligent technique as input determining the location of the fault zone. The intelligent technique used is a combination between Fuzzy Logic (FL) and Neural Network (NN) which called Adaptive Neuro Fuzzy Inference System (ANFIS). Training and testing data have been carried out by running a short circuit fault simulation with distance variations in the of fault location . The training process in ANFIS is carried out with many iterations. The ANFIS output shows the accuracy target of location fault, the small and good error value. Performs the ANFIS validation process in the form of RMSE and MAE values based on the type of asymmetric 4 power transmission line. The ANFIS validation result in the values of RMSE and MAE for one phase to ground short circuit that is 0,006472 and 0,005453. The result of ANFIS validation in the two phase short circuit between RMSE and MAE values that is 0,005046 and 0,004201. In the for two phase to ground short circuit of RMSE and MAE values from the ANFIS validation result that is 0,007294 and 0,006535. The comparison of the calculation results of this validation values between RMSE and MAE show that the results of ANFIS network testing. Smaller result of error value RMSE or MAE so the ANFIS network gets better, and vice versa. The comparison result shows that, using MAE methode can determine the location of the fault zone nearer than RMSE methode.Keywords : ANFIS, error, fault asymmetric, fault zone, transmission system